Peran Orang Tua Dalam Mendidik Anak Berdasarkan Kitab Ulangan 6:4-9 - Ligan, Lukas (Harati: Jurnal Pendidikan Kristen, 2022)
Educating children is a must for parents, because parents are responsible to God. Parents cannot make busy work an excuse for not educating their children in God, and regard it as the duty and responsibility of the school and church. Being a parent means taking on a great responsibility, namely educating children in all aspects. This responsibility is not something that is easily delegated to other parties, such as schools or churches, but is something that is integral to the life of every parent. The growth and development of children's knowledge will depend on the role of parents. This article tries to provide an understanding regarding the main role of parents in educating children based on the book of Deuteronomy 6:4-9. First, parents introduce God to their children through teaching, secondly teach God's commands repeatedly and thirdly, become an example in loving God. This article uses descriptive qualitative research with a literature and biblical text approach and focuses on discussing the role of parents in educating children based on Deuteronomy 6:4-9. Mendidik anak adalah sebuah keharusan bagi para orang tua, karena orang tua bertanggung jawab kepada Tuhan Allah. Orang tua tidak bisa menjadikan kesibukan bekerja menjadi alasan untuk tidak mendidik anak-anak di dalam Tuhan, dan mengangap hal itu sebagai tugas dan tanggungjawab pihak sekolah maupun gereja. Menjadi orang tua berarti mengemban Tanggung jawab yang besar yaitu mendidik anak dalam segala aspek. Tanggungjawab ini bukanlah merupakan sesuatu yang dengan mudah saja dilimpahkan ke pada pihak lain, seperti sekolah maupun gereja, melainkan merupakan sesuatu yang terintegral dalam kehidupan setiap orang tua. Tumbuh kembang dan pengetahuan anak akan sangat bergantung pada peran orang tua. Artikel ini mencoba memberi pemahaman terkait Peran utama orang tua dalam mendidik anak berdasarkan kitab Ulangan 6:4-9. Pertama orang tua memperkenalkan Tuhan kepada anak melalui pengajaran, kedua mengajarkan perintah Tuhan secara berulang-ulang dan yang ketiga menjadi Teladan dalam mengasihi Tuhan. Artikel ini mengunakan penelitian kualitatif deskriptif dengan pendekatan pustaka dan teks Alkitab dan berfokus pada pembahasan mengenai Peran orang tua dalam mendidik anak berdasarkan Ulangan 6:4-9.